Sraffa, Leontief, Lange: The political economy of input–output economics - Tiago Camarinha Lopes; Henrique Dantas Neder (EconomiA, 2017)
The fields of Political Economy and Input–Output economics are commonly unrelated due to the discrepancy between the qualitative and quantitative analysis in economic science. With the aim to overcome this separation, this paper relates the basic model of Production of Commodities by Means of Commodities to the paradigm of planning as the substitute for the market by sketching the logical-historical development of Input–Output economics. The model of Sraffa, the Leontief matrices and the Political Economy of Marxist tradition, represented by Oskar Lange, are strongly associated so that the typical qualitative concepts of planning, law of value and historical development of the capitalist system can be connected to the quantitative framework of matrix, programming and mathematical formalization. – – Os campos da Economia Política e da Economia do Insumo-Produto n\~ao s\~ao geralmente relacionados devido à discrepância entre as análises qualitativas e quantitativas na ciência econômica. Com o objetivo de superar essa separaç\~ao, o artigo relaciona o modelo básico de Produç\~ao de Mercadorias por Meio de Mercadorias com o paradigma da planificaç\~ao enquanto substituto do mercado ao descrever o desenvolvimento lógico-histórico da Economia do Insumo-Produto. O modelo de Sraffa, as matrizes de Leontief e a Economia Política de tradiç\~ao Marxista, representada por Oskar Lange, s\~ao associadas fortemente de modo que os conceitos tipicamente qualitativos de planificaç\~ao, lei do valor e desenvolvimento histórico do sistema capitalista possam ser conectados ao mundo quantitativo das matrizes, da programaç\~ao e da formalizaç\~ao matemática."
Keywords: 330; Political economy; Value theory; History of economic thought; Sraffa; Leontief; Marx; Teoria do Valor; História do Pensamento Econômico; Sraffa; Leontief; Marx